2019
DOI: 10.18203/2320-6012.ijrms20191317
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Bacillus clausii and multistrain probiotics in the management of acute diarrhoea in children

Abstract: Background: Diarrhoea is the second most common cause of under-five mortality especially in developing world. Many studies have been conducted so far using different probiotic strains with variable outcome. So, the aim of the present study was to compare the clinical efficacy of Bacillus clausii and multi strain probiotic formulation as adjunct treatment of acute diarrhoea.Methods: This prospective single blind randomized controlled clinical trial included 300 infants and children between 6 months to 6 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Similarly, B clausii ( A. clausii 088AE) showed their efficacy for managing diarrhea caused by broad-spectrum antibiotics in both children and adults [ 27 ]. Treatment with probiotic strains of B. clausii were also effective in reducing main clinical symptoms of acute diarrhea, including rotavirus-associated diarrhea in children [ 28 , 29 , 30 , 31 ]. In a recently published prospective study, B. clausii (O/C, N/R, SIN and T) was beneficial for managing symptoms of IBS in children [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, B clausii ( A. clausii 088AE) showed their efficacy for managing diarrhea caused by broad-spectrum antibiotics in both children and adults [ 27 ]. Treatment with probiotic strains of B. clausii were also effective in reducing main clinical symptoms of acute diarrhea, including rotavirus-associated diarrhea in children [ 28 , 29 , 30 , 31 ]. In a recently published prospective study, B. clausii (O/C, N/R, SIN and T) was beneficial for managing symptoms of IBS in children [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a prospective, single-blind, randomized controlled trial, Hamid et al [ 72 ] randomized 300 infants and children (aged 6 months to 6 years) with acute watery diarrhea to standard of care treatment alone or in combination with B. clausii (O/C, N/R, SIN and T; 2 × 10 9 CFU) b.i.d. for 5 days or a multi-strain probiotic once a day for 5 days ( n = 100 per group).…”
Section: Resultsmentioning
confidence: 99%
“…The clinical studies we identified in this narrative literature review of B. clausii probiotics and GI health largely support the beneficial effects of B. clausii for managing a variety of GI disorders and their symptoms. From preliminary observations of early clinical studies to recent and robustly designed clinical trials, randomized placebo-controlled trials and meta-analyses and pooled analyses, the evidence indicates that B. clausii is effective for treating and/or preventing antibiotic-associated diarrhea in adults and children [ 63 68 ] and acute diarrhea in adults [ 81 – 83 ], with most, but not all [ 70 , 73 ], studies supporting the effectiveness of B. clausii in acute childhood diarrhea [ 69 , 71 , 72 , 74 80 ]. Evidence from these studies and clinical use over many decades indicates that B. clausii is safe and well tolerated in adults and children [ 29 ].…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…B. clausii has demonstrated beneficial effects in adults, such as in ameliorating bacterial overgrowth [ 12 ], acute diarrhea [ 13 , 14 ], diarrhea associated with Clostridium difficile [ 15 ], and as an adjuvant in treating Helicobacter pylori [ 16 , 17 ]. Importantly, benefits of B. clausii have also been demonstrated in children, such as in antibiotic-associated diarrhea [ 18 , 19 ], diarrhea [ 13 , 14 , 20 25 ], and rotavirus-associated diarrhea [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%